Genetic Diversity and Screening of Rice (Oryza sativa L.) Genotypes for Drought Tolerance at Reproductive Phase - Pervin, MS; Halder, T; Khalequzzaman, M; Kader, MA; Aditya, TL; Yasmeen, R (Bangladesh Rice Journal, 2018)
Drought is a major abiotic constraint for growing rain-fed rice in Bangladesh. A total of 175 rice genotypes were evaluated using field-managed screening protocol to identify reproductive phase drought tolerant genotypes at Bangladesh Rice Research Institute, Gazipur, Bangladesh. Twelve morpho-physiological characters viz, growth duration, plant height, tiller number per plant, panicle number per plant, panicle length, filled grain number per plant, sterility percentage, filled grain weight per plant, 1000 grain weight (TGW), straw weight per plant, harvest index (HI) and percent yield reduction were recorded. Multivariate analysis was carried out by using software Genstat 5.5 to measure genetic divergence among the rice genotypes. In total 175 genotypes were constellated into ten clusters in which the cluster I exhibited maximum genetic distances from cluster V and the lowest genetic distance was between cluster II and X. Inter-cluster distances were higher than the intra-cluster distances suggesting wider genetic diversity among the genotypes of different clusters and homogeneity among the genotypes within the cluster. Among the 12 studied characters percent yield reduction contributed maximum towards total divergence in the genotypes, which revealed that these parameters contributed more to grain yield under drought stress. The genotypes of cluster I namely Canthi bakla (BRRI Genebank Acc. No. 7279), Nizersail (BRRI Genebank Acc. No. 7281), Hashim (BRRI Genebank Acc. No. 7283), Uricheora (BRRI Genebank Acc. No. 7311), Goura Kajol (BRRI Genebank Acc. No. 7312), Chini Sail (BRRI Genebank Acc. No. 7343), Tall Biruin (BRRI Genebank Acc. No. 7355), Sakkar Khora (BRRI Genebank Acc. No. 7506) and Boaincha Biruim (BRRI Genebank Acc. No. 7573) performed better under drought stress, which could be used in the crossing programme as donor parent for the development of variety Bangladesh Rice j. 2017, 21(1): 27-34